La retirada de la razón - Martínez Bonati, Félix (Revista Chilena de Literatura, 2016)
En este trabajo se traza un bosquejo de la presente situación intelectual, caracterizada como relativización de la racionalidad, y sus consecuencias: el llamado multiculturalismo y la incertidumbre e indefensión de principios cognoscitivos y éticos. Se sugiere reafirmar la posición universalista del estudioso latinoamericano y revisar el concepto de cultura europea. In this paper the author presents a description of the intellectual climate of the times. He finds it characterized by the relativization of rationality. Its consequences are so-called multiculturalism and the uncertainty and defenselessness of cognitive and ethical principles. Some suggestions address the position of Latinamerican thought and the concept of European culture.